Double-diffusive natural convection in an inclined enclosure with heat generation and Soret effect. Issue 8 (25th October 2018) - Hasnaoui, Safae; Amahmid, Abdelkhalek; Raji, Abdelghani; Beji, Hassen; Hasnaoui, Mohammed; Dahani, Youssef; Benhamed, Haykel
Abstract : Purpose: The purpose of this paper is to study numerically thermosolutal natural convection within an inclined rectangular cavity in the presence of Soret effect and heat generation. The enclosure is heated and salted from its long sides with constant but different temperatures and concentrations. The study focuses on the effects of three main parameters which are, the Soret parameter ( Sr  = 0 and –0.5), the internal to external Rayleigh numbers ratio 0 ≤  R  ≤ 80 and the cavity inclination γ, varied from 0° (vertical position) to 60°. The combined effects of these parameters on fluid flow and heat and mass transfer characteristics are examined for the external Rayleigh number RaE  = 10 5, the Prandtl number Pr  = 0.71, the buoyancy ratio N  = 1, the Lewis number Le  = 2 and the aspect ratio of the cavity A  = 2. Design/methodology/approach: A hybrid lattice Boltzmann-finite difference method (LBM-FD) was used to tackle the problem under consideration. The LBM with the simple relaxation time was used for the fluid flow in the presence of the gravity force, while the temperature and concentration equations were solved separately using an explicit finite-difference technique at the Boltzmann scale. Findings: The monocellular nature of the flow, obtained for R  = 0 is not destroyed by varying the cavity inclination and the Soret parameter but rather by the increase of the parameter R. The Soret parameter and the cavity inclination become perceptible at high values of R . The inclination γ  = 60° leads to high mean temperatures compared to the other inclinations. The effect of R on mean concentration is amplified in the presence of Soret effect but limited in the absence of the latter. The negative Soret parameter combined with high internal heat generation and a relatively high inclination is important when the objective is to maintain the fluid at a high concentration of species. The presence of bicellular flow combined with the important elevation undergone by the fluid temperature, makes both the cold and hot walls playing a cooling role with the most important exchanges taking place at the upper part of these walls. The analysis of the mean mass transfer shows that the increase of the inclination may lead to an increase or a decrease of the mass transfer depending on the range of R, in the case of Sr = 0. However, for Sr = −0.5, it is observed that the increase of γ is generally accompanied by a reduction of the mass transfer. Originality/value: To the best of the authors' knowledge, the hybrid LBM-FD was not used before to study such a problem. Combined effect of R and inclination may be useful in charging the fluid with species when the objective is to maintain high concentrations in the medium.